THE IMPLICATION OF ETHNOMEDICAL UNDERSTANDING ON THE CONSERVATION OF MEDICINAL PLANTS VOCABULARY IN THE SOUTH KUTA COMMUNITY - Andiani, Dyah; Rasna, I Wayan; Suandi, I Nengah (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2019)
This study aimed to find out (1) ethnomedical understanding on the conservation of medicinal plants vocabulary in the South Kuta community, (2) the implication of ethnomedical understanding on the conservation of medicinal plants vocabulary in the South Kuta community. The design of this study was descriptive research design. The subjects in this study were 200 people. The objects in this study were in the form of understanding of the ethnomedical vocabulary, medicinal plants, and the implications of ethnomedical understanding on the preservation of vocabulary on traditional medicinal plants. Data collection were conducted by distributing questionnaires, interviews, document recording, and observation. Data analyses were conducted by the descriptive method of quantitative and qualitative. The presentation was done formally and informally. The results showed that the percentage of understanding which was very dominant or above 50%are aloe vera, turmeric, ginger, and kencur. The implications of ethnomedical understanding on vocabulary preservation of medicinal plants for the people of South Kuta include vocabulary linkages, the making of traditional medicines, the making and utilization of them, such as the manufacture and use of herbs for traditional medicine made from turmeric, dadap, aloe vera, ginger, and kencur. Making vegetables, from Moringa leaves, and dadap which is mashed and pasted/smeared, andong, dadap, kelor, turmeric, ginger, kencur. In addition, the manufacture of scrubs from turmeric, and kencur. Words of traditional medicinal plants which were not listed in implication mean the community just understood or knew but the implementation related to ethnomedical had not been done. In short, the percentage of public understanding which is dominant or above 50% is the understanding of the word of aloe vera, turmeric, ginger, and kencur. The implications of the ethnomedical understanding of vocabulary preservation of medicinal plants of the people of South Kuta include the linkage of vocabulary to the manufacture of traditional medicines and their utilization, such as the manufacture and use of herbs for traditional medicine made from turmeric, dadap, aloe vera, ginger, and kencur.